A Critical Queer Discourse Analysis of Sexual Orientation Secrecy Represented in “Love Simon” - Anna Riana Suryanti Tambunan; Emia Glory Sembiring (English Department - University of Sultan Ageng Tirtayasa, 2022)
The objectives of this study were to investigate the influence of sexual orientation secrecy from the utterances of main characters and author’s narration and the realization of the influence of sexual orientation found in Love Simon movie. The study was conducted using a critical discourse analysis approach. The data of this study were taken from the transcript of Love Simon. The data of this study were the main character’s utterances and author’s narration that appeared in Love Simon that can categorize into kinds of sexual orientation secrecy based on romantic secrecy. The data analysis was taken by identifying, classifying, and analysing the data. The findings indicated 6 kinds of romantic secrecy of sexual orientation that were flouted by the main characters and author’s narration in Love Simon. Based on the research findings, the most frequent utterances were the break-up distress. This proves that the sexual orientation secrecy gives a negative influence on the main character in this movie.